Analisis Yuridis Terkait Pembentukan Komponen Cadangan Sebagai Pertahanan Pendukung Negara Ditinjau Dari Prespektif HAM - Riyanto Riyanto; Muhammad Anwar Ibrahim; Muhammad Fahrudin; Irwan Triadi (Lembaga Pengembangan Kinerja Dosen, 2023)
The defence and security of the Indonesian state is a very crucial thing in the practice of the state so that it requires a component of citizens to participate in efforts to maintain state security in addition to the Indonesian National Army (TNI) and the Indonesian National Police (Polri), the Supporting Component is needed in efforts to defend and secure the state but in practice the community thinks that it is contrary to Human Rights (HAM). The purpose of this study is to carefully examine and analyse the Establishment of the Reserve Component as a State Supporting Defence Viewed from a Human Rights Perspective. The legal research method used is normative juridical legal research method by conducting research on library materials and using a statute approach. The results of the research are that in the Indonesian constitution, the rights and obligations to defend the country by citizens have been regulated through the 1945 Constitution of the Republic of Indonesia, Law No. 3 of 2023 concerning State Defence, Law No. 23 of 2019 concerning Management of National Resources for State Defence, as well as the embodiment of patriotism in the state that can be carried out by a citizen who is then made by the Indonesian Government a state defence system in order to support national defence, namely by implementing a Reserve Component system stipulated in the PSDN Law and the formation of the Reserve Component is not an element of coercion or a form of human rights violation.